2010
DOI: 10.1039/c0gc00263a
|View full text |Cite
|
Sign up to set email alerts
|

Production of jet and diesel fuel range alkanes from waste hemicellulose-derived aqueous solutions

Abstract: In this paper we report a novel four-step process for the production of jet and diesel fuel range alkanes from hemicellulose extracts derived from northeastern hardwood trees. The extract is representative of a byproduct that could be produced by wood-processing industries such as biomass boilers or pulp mills in the northeastern U.S. The hemicellulose extract tested in this study contained mainly xylose oligomers (21.2 g/l xylose after the acid hydrolysis) as well as 0.31 g/l glucose, 0.91 g/l arabinose, 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
228
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(236 citation statements)
references
References 41 publications
3
228
3
Order By: Relevance
“…In addition to using biphasic solvent systems, most notably water and tetrahydrofuran, [3] processes such as Suprayield [15] aim to produce high yields of furfural by rapidly removing furfural vapor away from xylose as it is being formed by adiabatic distillation. Presently, only orthophosphoric acid is used as the catalyst in the Suprayield process due to corrosion problems associated with other mineral acids.…”
Section: Reactivity Of the Nafion 117 Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to using biphasic solvent systems, most notably water and tetrahydrofuran, [3] processes such as Suprayield [15] aim to produce high yields of furfural by rapidly removing furfural vapor away from xylose as it is being formed by adiabatic distillation. Presently, only orthophosphoric acid is used as the catalyst in the Suprayield process due to corrosion problems associated with other mineral acids.…”
Section: Reactivity Of the Nafion 117 Catalystmentioning
confidence: 99%
“…Other major drawbacks to mineral acids include: the occurrence of extensive side reactions from long reaction times that reduce furfural yield; neutralization of the spent acid; and technological challenges in the development, use, and maintenance of equipment exposed to the corrosive liquids. As part of a four-step process for the formation of jetand diesel-fuel-range alkanes, Xing et al [3] reported the synthesis of furfural from HCl-catalyzed biphasic dehydration of hemicellulose extracts at 87 % yield. However, they acknowledge that the high cost of producing such alkanes could be reduced by using solid acids in place of HCl.…”
Section: Introductionmentioning
confidence: 99%
“…One suggested strategy is the chemical transformation of this waste into valuable products such as furfural and carboxylic acids (Xing et al 2011 (Xing et al 2010). However, these processes are highly dependent on the purity of the waste stream and face several challenges before being scaled up.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In this context, microalgae are considered as one of the most promising renewable energy resources owing to their short harvest cycle, small cultivation area, high lipid content (up to 80% of their dry weight) and minimum greenhouse gas emission. [3,4] The major components of microalgal oil are free fatty acids (FFAs) and triglycerides.…”
Section: Introductionmentioning
confidence: 99%